2018
DOI: 10.3390/ijms19123986
|View full text |Cite
|
Sign up to set email alerts
|

An Animal Model for Assessing the Effects of Hydroxyurea Exposure Suggests That the Administration of This Agent to Pregnant Women and Young Infants May Not Be as Safe as We Thought

Abstract: The cytostatic agent hydroxyurea (HU) has proven to be beneficial for a variety of conditions in the disciplines of oncology, hematology, infectious disease and dermatology. It disrupts the S phase of the cell cycle by inhibiting the ribonucleotide reductase enzyme, thus blocking the transformation of ribonucleotides into deoxyribonucleotides, a rate limiting step in DNA synthesis. HU is listed as an essential medicine by the World Health Organization. Several studies have indicated that HU is well tolerated a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…HU can cause abnormal embryonic development in mice, rats, and New Zealand white rabbits [4][5][6][7][8][9]. Moreover, studies have shown that use of HU in pregnant women or babies can cause harmful effects [10,11]. In addition, HU can be extremely toxic to preimplantation embryos because it impacts blastocyst formation and development, compromises folliculogenesis, and reduces ovulation [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HU can cause abnormal embryonic development in mice, rats, and New Zealand white rabbits [4][5][6][7][8][9]. Moreover, studies have shown that use of HU in pregnant women or babies can cause harmful effects [10,11]. In addition, HU can be extremely toxic to preimplantation embryos because it impacts blastocyst formation and development, compromises folliculogenesis, and reduces ovulation [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, HU can be extremely toxic to preimplantation embryos because it impacts blastocyst formation and development, compromises folliculogenesis, and reduces ovulation [12]. HU inactivates ribonucleotide reductase and inhibits DNA synthesis in proliferating cells, and can increase apoptosis and induce cell cycle changes [11,13,14]. Accordingly, HU exposure induced apoptosis of fetal tissue cells, which resulted in abnormal tissue development in offspring [15].…”
Section: Introductionmentioning
confidence: 99%